Isolasi Senyawa Turunan Kuinon dari Tanaman - Kurnia, Klaritya Anisya; Widyatamaka, Shafa Qotrunnada; Paujiah, Shipa; Prayuda, Erlangga Muhamad (Ridwan Institute, 2021)
Indonesia is an archipelago with a wealth of flora where 7,000 types of medicinal plants have various properties. With this biodiversity there is also chemical diversity such as secondary metabolites and one of them is quinones. This review article was created with the aim of providing information and evidence regarding the isolation found in plants suspected of having quinone-derived compounds. The isolation of quinone derivatives can be carried out by extraction, fractionation, and isolation methods using different solvents and methods. The method used in this review is based on analytical literature study which was analyzed from several scientific publications in national and international journals. The results obtained showed that isolates from aloe vera, bisbul, mengkudu, hedyotis caudatifolia Merr and ceratotheca triloba plants showed positive responses to the tests carried out, so it can be concluded that each plant contains quinone derivative compounds.